The role of ornamental plants as hosts of Tomato chlorotic spot virus and its vector thrips affecting tomato production. Issue 5 (12th March 2023) - Khan, Rafia A.; Seal, Dakshina R.; Zhang, Shouan; Liburd, Oscar E.; Srinivasan, Rajagopalbabu; Colee, James
Abstract: The tomato industry in South Florida (USA) is seriously affected by recently emerging Tomato chlorotic spot virus (TCSV). Western flower thrips, Frankliniella occidentalis (Pergande), and common blossom thrips, Frankliniella schultzei (Trybom) (Thysanoptera: Thripidae), are the two known vectors of TCSV in Florida. In the present study, the presence of thrips vectors and TCSV in 24 flowering ornamental plant species was observed in South Florida. The two thrips vectors, as well as melon thrips, Thrips palmi Karny (Thysanoptera: Thripidae), were abundant in the area; they were observed with a range from high (83.1 per sample of 10 flowers) in Hibiscus rosa‐sinensis L. to low (3.7 per sample of 10 flowers) in Catharanthus roseus (L.) G. Don in a nursery study. In a subsequent greenhouse study, we selected seven species of ornamentals, among which the species with the highest thrips abundance, and planted them next to tomato, to determine their effects on TCSV incidence and thrips abundance in tomatoes. Tomatoes with Portulaca oleracea L. next to them showed a higher number of TCSV‐infected plants (4.25 plants per plot in 2017, and 3.25 plants per plot in 2018) compared to tomatoes with some of the other ornamentals next to them. We report the presence of TCSV through reverse transcriptase polymerase chain reaction (RT‐PCR) analysis in Lantana camara L., H. rosa‐sinensis, Mandevilla spec., Gazania linearis (Thunb.) Druce, Hemerocallis spec., Agastache spec., and P. oleracea . Identification of alternative hosts of TCSV and thrips vectors can be helpful to evaluate the ongoing management programs and develop future programs in local tomato‐growing areas. Abstract : Tomato chlorotic spot virus (TCSV), vectored by thrips, is an important disease of tomato in South Florida, USA. We investigated the presence of thrips and TCSV in 24 ornamental plant species. Thrips, mainly Frankliniella occidentalis and Frankliniella schultzei (Thysanoptera: Thripidae), were found in high abundance in ornamental flowering plants in a nursery study. In a greenhouse study, tomatoes had the highest TCSV incidence when Portulaca oleracea was planted next to them. These ornamentals could function as a reservoir for the virus.